Ethephon Induced Gummosis in Bombax ceiba L. and Sterculia urens Roxb. - Babu, A. M.; Menon, A. R. S. (Indian Forester, 1989)
In the present study, ethephon was administered to Bombax ceiba and Sterculia urens. The optimum concentration of ethephon for maximum yield of the exudate without visible adverse effect on the plant is worked out.